PLOT IN A COLLECTION OF SHORT STORIES “SAKINAH BERSAMAMU” WRITTEN BY ASMA NADIA WITH FEMINIMISM ANALYSIS - Noermanzah Noe Noermanzah (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2017)
PLOT DALAM KUMPULAN CERPEN SAKINAH BERSAMAMU KARYA ASMA NADIA DENGAN ANALISIS FEMINIMISMEAbstractThis study aims to obtain an understanding about the plot in a collection of short stories "Sakinah Bersamamu" by Asma Nadia. This study used a qualitative approach assisted by analysis of feminism. Documentation and observation are used in the data collection technique. Research data are in the forms of plot, stage of plot, and a form of conflict, and the form of completion in a collection of short stories "Sakinah Bersamamu" by Asma Nadia. The results of research isthe plot in the short story collection Sakinah Bersamamu by Asma Nadia, they generally have two forms: the form of plot forward and plot backward, with the stages of starting point with a simple introduction, conflict, recognition of conflict, complication, denouement, and resolution. Forms of conflicts in the collection of short stories in the form of inner conflict and the solution is in the form of closed and open. Plot presented by Asma Nadia in a collection of short stories "Sakinah Bersamamu" is able to bring the event-by-event of problems about the conflict in the household, ranging from problems in social life, the problems of the family, especially the husband, and the problems of the past.Keyword: plots, the short story collection, feminisme analysis AbstrakPenelitian ini bertujuan untuk memperoleh pemahaman tentang plot dalam kumpulan cerpen ”Sakinah Bersamamu” karya Asma Nadia. Penelitian ini menggunakan pendekatan kualitatif dengan dibantu analisis feminisme. Teknik pengumpulan data menggunakan teknik dokumentasi dan observasi. Data penelitian berupa bentuk plot, tahapan plot, dan bentuk konflik, dan bentuk penyelesaian dalam kumpulan cerpen ”Sakinah Bersamamu” karya Asma Nadia. Hasil penelitian yaitu plot dalam kumpulan cerpen Sakinah Bersamamu karya Asma Nadia, secara umum memilik dua bentuk yaitu berbentuk plot maju dan berbentuk plot mundur, dengan tahapan dimulai dengan pengenalan sederhana, konflik, pengenalan penyebab konflik, komplikasi, peleraian, dan penyelesaian. Bentuk konflik dalam kumpulan cerpen berupa konflik batin dan penyelesaiannya berbentuk tertutup dan terbuka. Plot yang dihadirkan oleh Asma Nadia dalam kumpulan cerpen “Sakinah Bersamamu” mampu menghadirkan peristiwa demi peristiwa tentang permasalahan dalam rumah tangga, mulai dari permasalahan dalam kehidupan sosial, permasalahan dari dalam keluarga terutama suami, dan permasalahan dari masa lalu.Kata kunci: plot, kumpulan cerpen, analisis feminisme